THE TENSOR DECOMPOSITION OF THE DATA MINING TECHNOLOGY: TIME SERIES ANALYSIS - Минаев, Ю. Н.; Гузий, Н. Н.; Филимонова, О. Ю.; Минаева, Ю. И. (Science-based technologies, 2016)
In the article method of intellectual analysis TS, realised in the manner of deciding the matrix equations, link consequent tensor-windows TS, at a level rate of univariate models is considered. Incorpo-rated generalise feature of minimum fragment. Deciding the matrix equations allow calculate invariants (traces, norms and others), matrixes of singular values, Frobenius distances between matrixes, define trands of traces, norms, distances; change of trand a sign of anomaly TS or falling out of conditions a rate.